Bacterial Biofilms 2020
DOI: 10.5772/intechopen.90176
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms Formed by Pathogens in Food and Food Processing Environments

Abstract: This chapter presents the ability of some pathogenic (Listeria monocytogenes, Escherichia coli, Salmonella enterica, Campylobacter jejuni, Pseudomonas aeruginosa) and toxigenic bacteria (Bacillus cereus, Staphylococcus aureus) to form biofilms and contribute to the persistence of these microorganisms in the food industry. Particularities regarding attachment and composition of biofilms formed in food and food processing environments are presented and genes involved in biofilm production are mentioned. To give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 182 publications
(119 reference statements)
0
24
0
Order By: Relevance
“…Foodborne pathogen bacteria that form biofilms are some spore-forming, Gram positive bacteria like B. cereus and B. subtilis as well Clostridium perfringens [33], nonsporogenic ones, Staphylococcus aureus and L. monocytogenes, and Gram negative food pathogens E. coli, Pseudomonas aeruginosa, Campylobacter jejuni [34], Shigella sp., Salmonella enterica, and Yersinia enterocolitica [35]. Biofilm formation by food pathogens is a well-known problem in food industry, and it is recently topic of numerous publications [32,36,37], but there are some additional inves-tigations that shall be discussed, especially in connection with recent foodomic investigations of these processes [36]. Our recent proteomic investigations led us to the conclusion that there are basic differences between Gram positive and Gram negative bacteria in reactions to environmental stress, at least at the proteome level [38][39][40] (see also Fig.…”
Section: Bacterial Biofilmsmentioning
confidence: 99%
See 4 more Smart Citations
“…Foodborne pathogen bacteria that form biofilms are some spore-forming, Gram positive bacteria like B. cereus and B. subtilis as well Clostridium perfringens [33], nonsporogenic ones, Staphylococcus aureus and L. monocytogenes, and Gram negative food pathogens E. coli, Pseudomonas aeruginosa, Campylobacter jejuni [34], Shigella sp., Salmonella enterica, and Yersinia enterocolitica [35]. Biofilm formation by food pathogens is a well-known problem in food industry, and it is recently topic of numerous publications [32,36,37], but there are some additional inves-tigations that shall be discussed, especially in connection with recent foodomic investigations of these processes [36]. Our recent proteomic investigations led us to the conclusion that there are basic differences between Gram positive and Gram negative bacteria in reactions to environmental stress, at least at the proteome level [38][39][40] (see also Fig.…”
Section: Bacterial Biofilmsmentioning
confidence: 99%
“…Biofilm matrix components of this bacterium are exopolysaccharides, proteins including some enzymes, and finally, surface protein A and the above-mentioned surface protein G [31,[44][45][46]. Grigore-Gurgu et al [37] reported about genes that are responsible for cell adhesion and further biofilm formation. In this process, activation of genes that are responsible for cell adhesion to the surface is followed by the activation of transporter proteins encoding genes [47][48][49].…”
Section: Gram Positive Bacteriamentioning
confidence: 99%
See 3 more Smart Citations